An Analysis of the Influence of Liquidity Ratios, Stock Prices, Profitability, and Capital Structure on Earnings Growth as an Intervening Variable: (Study on Food and Beverage Companies' Firm Values) - Adelia Khoirunnisa; Lia Nirawati (Jurnal Manajemen Bisnis, 2024)
Investment in the food and beverage (F&B) sector has become increasingly popular. This study analyzes the impact of financial ratios on the firm value of F&B companies listed on the IDX during the 2019-2023 period. The results show that the liquidity ratio (X1) and capital structure (X3) significantly influence firm value (Y) through the mediation of company growth (Z). Conversely, stock price profitability (X2) does not significantly impact firm value (Y) through the mediation of earnings growth (Z). These findings suggest that investors should consider these ratios when making investment decisions, as they can optimize their portfolios and achieve long-term financial goals. This research contributes to the financial literature by providing empirical evidence on the factors affecting firm value in the F&B sector in Indonesia. Additionally, intelligent investing can yield optimal financial returns for investors.